2020
DOI: 10.1186/s13063-020-04852-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Keluoxin capsule combined with losartan potassium on diabetic kidney disease: study protocol for a randomized double-blind placebo-controlled multicenter clinical trial

Abstract: Background Diabetic kidney disease (DKD) is one of the most important microvascular complications of diabetes, and its prevalence has increased dramatically in the past few decades. DKD is responsible for considerable morbidity and mortality of patients with diabetes. Keluoxin capsule (KLX) is a Chinese patent medicine that has been used in the clinic to control DKD for years. Previous studies have shown that KLX appears to reduce proteinuria, but the study protocols as well as the primary outcome need to be i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thirteen studies [ 8 – 12 , 14 , 15 , 20 , 21 , 24 , 26 – 28 ] analyzed blood urea nitrogen (BUN). Meta-analysis showed that MD = −0.47, 95% CI (-0.72, -0.22), P = 0.0002, and I 2 = 72%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies [ 8 – 12 , 14 , 15 , 20 , 21 , 24 , 26 – 28 ] analyzed blood urea nitrogen (BUN). Meta-analysis showed that MD = −0.47, 95% CI (-0.72, -0.22), P = 0.0002, and I 2 = 72%.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 6 , 8 , 13 , 16 , 28 , 29 , 31 ] analyzed glycosylated hemoglobin. Meta-analysis showed that there was no significant difference in the treatment of glycosylated hemoglobin in patients with diabetic nephropathy by JSBC MD = −0.14, 95% CI (-0.03, -0.24), P = 0.02, and I 2 = 3 ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Keluoxin capsule is a Chinese herb compound preparation for treatment of qi and yin deficiency and blood stasis in DKD (125). A meta-analysis for DKD found that Keluoxin capsule improved the levels of serum creatinine and lipid (126).…”
Section: Chinese Herb Compound Preparations In Attenuating Renal Inju...mentioning
confidence: 99%
“… 13 , 14 Losartan potassium (Los), a classic ARB, has been shown to exhibit renal protective effects in DKD. 15 , 16 Moreover, Los was found to reduce blood pressure and attenuate kidney fibrosis in mice with CKD. 17 However, the clinical application of ARBs is limited, because of their side effects including dry cough and elevated serum potassium level.…”
Section: Introductionmentioning
confidence: 99%